JAVANESE VILLAGE WISDOM: AN ANALYSIS OF TWO STORIES BY TURIYO RAGILPUTRA - Yoseph Bambang (Celt: A Journal of Culture, English Language Teaching & Literature, 2004)
This paper present an analysis of two short stories by the contemporary Javanese poet and short story writer Turiyo Ragilputra. These stories were originally written in Javanese during the 1990s. Like most modern literary works in Javanese, these stories are about the lives of ordinary people in contemporary rural Java. However, the incidents in the stories are not simple. Lives in contemporary rural Java-the most modern pat of Indonesia-have become complicated and different from how they used to be. During the 1990s, particularly, Indonesia underwent many significant economic, political, and social changes, and these changes-which actually started to begin in 1960s (Anderson, 1965)-affected the lives of common people in rural areas. In these stories, Turiyo Ragilputra records these changes in rural Central Java trough the incidents and the relationship among the characters. In a way, it is trough the incidents and the relationship of the characters of the stories that we can take a closer look at the contemporary rural Javanese lives, culture, and values. In addition, we can also take a closer look at what kinds of problems contemporary Javanese villagers have.